(untitled) (The Journal of Psychology and Sociology, 2019)
Today new approaches in management of organizations are required, as change in conditions of production have been increased (acceleration of innovations, search of highly skilled personnel, close interaction of technological, social, economic and political processes, their global impact on economy). These changes also affect the scope of psychology, in particular, psychology of personality and organizational behavior. Organizational behavior is a systematic studying and practical knowledge of interaction of individuals and groups of people in organization. Organizational behavior is the field of scientific research regarding the reasons and factors of people’s behavior in the organization. In this article modern foreign research on this subject are considered. It is revealed that 17% from articles that we analyzed are devoted to the review of historical development of organizational psychology. 77% of publications are devoted to research of the personality and organizational behavior with use of a Big Five methodology and methods of neuroscience. Emergence of new concepts, such as positive organizational behavior, strategic organizational behavior, and also often found concept of organizational citizenship behavior is reflected. Works of the Kazakhstani authors have made 6%. Generally the comparative review of the Kazakhstan, American, Japanese and Russian mentality is carried out. As a result of the analysis of articles devoted to the personality and organizational behavior the conclusion regarding the following tendencies in modern world organizational psychology has been drawn: 1) big variety of theoretical bases and methodical approaches to studying of the personality and organizational behavior; 2) steady tendency of use of Big-Five as a personality methodology; 3) application of more modern methods (computer options of questionnaires, neuropsychological approaches, statistical data processing) along with classical methods of research of organizational behavior (questionnaires, tests, an observation method); 4) there is lack of implementation of modern methods in the Kazakhstani organizational psychology, they aren’t used widely. This article can be useful for teachers, students, and also for specialists in the field of management of organizations and HR managers.